(3GdfXQjI GdYGeI ddLRGA aj GdbGfhf GdOhdj GdYGe (B/s - (3CHh YjWI, GdSjO,s 1965- ((3GdbGgQI (B:s (3OGQ eUQ ddfTQ hGdJhRjY,s, 2025)
(3jecffG Gdbhd, Cfg EPG CQGOJ GdEfSGfjI GdJbOe hGdCef hGdSdGe, aEfg djS ef Md CeGegG Shi GdJedc HCgOGH fXQjI GdLRGAGJ GdOhdjI, agj Jdc GdYUG GdSMQjI, GdJj HecfJgG JMbjb LejY Gdbje GdYdjG GdfRjgI GdJj JSYi GdLeGYI GdOhdjI Edi JMbjbgG, hYdi VhA Pdc aEffG Sha fJfGhd aj gPG GdcJGH, GdehVhYGJ GdBJjI aj GdHGH GdJegjOj fJfGhd cfg GdLRGA aj GdbGfhf GdOGNdj hGdbGfhf GdYGe GdOhdj, haj GdbSe GdChd ef gPg GdOQGSI fJfGhd ehVhY GdJCUjd GdbGfhfj dacQI GdLRGA aj GdbGfhf GdOhdj GdYGe hfYGdL ajg ehVhYjf geG GdVhGHW GdbGfhfjI dacQI GdLRGAGJ GdOhdjI, hGdOhQ GdNdGb deUGOQ GdbGfhf GdOhdj GdYGe aj EQSGA GdLRGAGJ GdOhdjI, haj GdbSe GdKGfj ef gPg GdOQGSI GdeJhGVYI fYGdL ehVhY GdeeGQSI GdJWHjbjI ddLRGAGJ GdOhdjI hLejY UhQ gPg GdLRGAGJ ef LRGAGJ LfGFjI hEOGQjI heOfjI, Ke fNJJe gPG GdcJGH HGdMOjK Yf GdeCehd dacQI GdLRGAGJ GdOhdjI(B.s
(3GdCUd CWQhMI OcJhQGg GdadSaI aj GdMbhb bSe GdbGfhf GdOhdj GdYGe HcdjI GdMbhb(B-(3LGeYI WfWG(B.s
(3jTJed Ydi HHdjhLQGajI(B.s
Keywords: (3GdbGfhf GdOhdj GdYGes; (3GdbGfhf GdOhdjs